Wykorzystanie warunkowego rozkładu Pearsona typu IV w modelowaniu skośności i leptokurtozy rozkładów stóp zwrotu - Piontek, Krzysztof (Modeling Skewness and Excess Kurtosis in Stock Returns Using Conditional Pearson Type IV Distribution, 2005)
The AR-GARCH models with conditional normal or Student's distributions are usually using to modelling many effects that occur in financial time series of returns. This two distributions are not sufficient to account for the skewness in the data. Therefore, there is a real need to use an asymmetric density that can be easily estimated and whose tails are sufficiently heavy. Pearson type TV density is such a distributions and additionally nests normal and Student's distributions. The results received from our research showed that for 30% of analysed instruments from Polish market the best model AR(1)-GJR-GARCH(1,1) model with Pearson type IV conditional distribution of errors. The results can be applied to risk measuring with Value at Risk method or to option pricing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 434-443